Implementasi Penyusunan Anggaran Bahan Baku Dengan Metode Economic Order Quantity (EOQ) Pada Batik Sekar - Abibah, Nur; Qomariyah, Siti Nur (CV. ITTC INDONESIA, 2023)
This study analyzes the Economic Order Quantity (EOQ) as a raw material budgeting in Batik Sekar Jati. The purpose of this study is to determine whether the raw material inventory control applied by UKM Batik Sekar Jati has optimal in emphasizing production costs, and to determine the minimum total inventory cost. This research uses descriptive method that is quantitative in nature. Descriptive analysis techniques used to analyze data on the problem of controlling the raw material budget in an effort to reduce production costs are using the Economic Order Quantity (EOQ) method. The results showed that the company can save costs if the company uses the EOQ method, where the ordering cost was lower than the ordering cost according to the method that the company was currently running. The optimal purchase of raw materials according to the company's actual data was more than the purchase according to EOQ which purchases less. For budget control of raw materials Batik Sekar Jati can use Economic Order Quantity (EOQ) analysis, Safety Stock (SS), Reorder Point (ROP) and Total Cost (TC).